GuanXi And Gender: Does It Matter To Marketing Performance? - Teoh , Siau Teng; Mohd Isa, Salmi (2016)
Purpose: The purpose of this paper is to propose a conceptual model in GuanXi and marketing performance linkage from the gender perspective. Design/ Methodology/ Approach: GuanXi is a concept of social networking that links personal to business relations to achieving personal or business gains. The paper proposes the conceptual framework based on an extensive review of literature on GuanXi and marketing performance from gender perspective. The discussion is on the construct and relational types of GuanXi as a cultural element, which are pertinent to Asian institutional settings. Since most of the previous research offers no explanation for GuanXi’s distinct contribution to marketing outcome, this paper proposes the use of marketing performance metrics in order to capture precisely the GuanXi outcome. Findings: Previous research on GuanXi or relational based studies to performance outcome often focuses on the firm’s overall performance evaluation. However, the findings are inconsistent and this could be due to the subjective characteristics of social capital being ignored. This paper conceptualizes the possible linkage of GuanXi construct and relational outcomes to marketing performance, subsequently contributing to the overall firm’s performance through the gender lens. Practical Implications: Based on the model that has been developed, the linkage between GuanXi-marketing performance relations would be able to assist the industry manager in identifying their marketing efforts in relation to the marketing performance outcomes. In addition, the managers can take the gender variance into consideration when formulating the marketing strategies for effective relationship marketing to their business counterparts. Originality/ Value: This paper is original in its attempts in proposing the linkage between GuanXi to marketing performance outcome from the gender perspective.